Pedagogic affect: assembling an affirming ethics. (8th August 2021) - Healy, Sarah; Mulcahy, Dianne
ABSTRACT: This article takes as its focus the doing of pedagogic affect. We are not so much concerned with what pedagogic affect is as what it does and how it might do more. We revisit Spinozist concepts of affect, as taken up by Deleuze and Braidotti, in the context of affirmative ethics. Bringing assemblage thinking together with empirical material generated through two qualitative research projects, we map affect-ethics relations within a classroom-citizenship-test assemblage and a kinetic-fungi-tower-sculpture assemblage. Pedagogic affect emerges as constitutive of ethical subjectivities in a nexus of affect, pedagogy and power. We argue that attending to affective and material-discursive relationality in all pedagogic processes affords a practice of response-able pedagogy and invites an ethics of affirmation that augments the affective capacities of learner- and teacher-bodies, enlarging their potential to engage in ethical action.